Meningkatkan School Well-Being di Era Digital (Pengabdian Masyarakat di SMA Muhammadiyah 1 Jakarta) - Anizar Rahayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Students' perceptions of the school environment need attention because they can indirectly affect students' efforts to achieve academic achievement. Therefore, schools always strive to create safe, comfortable, fun, and not dull conditions, known as school well-being, which is the development of the concept of well-being. This community service activity was carried out for class X IIS 2 SMA Muhammadiyah 1 Jakarta, who felt less happy because they could not follow lessons using information technology in their teaching and learning activities. This community service aims to improve students' school well-being so that with the happiness they feel, students are more enthusiastic and motivated to improve their learning achievement at school. This activity is carried out in the form of counseling. The results obtained from this activity are an increase in students' understanding of school well-being and creating a sense of happiness in the teaching and learning process.